A narrative review of pregnancy after malignancies in young women that don't originate in the female genital organs or in the breast. (March 2021) - Girardelli, Serena; Mangili, Giorgia; Cosio, Stefania; Rabaiotti, Emanuela; Fanucchi, Antonio; Valsecchi, Luca; Candiani, Massimo; Gadducci, Angiolo
Graphical abstract: Abstract: While cancer during pregnancy and its treatment has grown to be a popular topic in recent years, little is known on how to advise patients looking to conceive or conceiving after cancer treatment. The aim of this paper is to review the available literature on the impact of pregnancy on survivors of the most common childhood cancers, brain cancer, haematological malignancies, thyroid cancer, melanomas and sarcomas. Its main objective is to be a source of information for clinicians looking to counsel patients in these delicate moments exploiting all the available literature, albeit scarce. Given the available literature, we conclude that the presence of a multidisciplinary team is of great importance in supporting the patient and her loved ones when facing pregnancy with a previous cancer diagnosis.